Genetic differentiation between humpback whales (Megaptera novaeangliae) from Atlantic and Pacific breeding grounds of South America. Issue 2 (18th November 2016) - Cypriano‐Souza, Ana Lúcia; Engel, Márcia H.; Caballero, Susana; Olavarría, Carlos; Flórez‐González, Lilián; Capella, Juan; Steel, Debbie; Sremba, Angie; Aguayo, Anelio; Thiele, Deborah; Baker, C. Scott; Bonatto, Sandro L.
Abstract: Humpback whales wintering in tropical waters along the Atlantic and Pacific coasts of the South American continent are thought to represent distinct populations or "stocks." Here we present the first analysis of genetic differentiation and estimates of gene flow between these breeding stocks, based on both mitochondrial DNA (mtDNA) control region sequences (465 bp) and 16 microsatellite loci from samples collected off Brazil ( n = 277) and Colombia ( n = 148), as well as feeding areas near the western Antarctic Peninsula ( n = 86). We found significant differentiation between Brazilian and Colombian breeding grounds at both mtDNA ( F ST = 0.058) and microsatellite ( F ST = 0.011) markers and corroborated previous studies showing genetic similarity between humpbacks from Colombia and those from Antarctic Peninsula feeding areas. Estimates of long‐term gene flow between Brazil and Colombia were low to moderate, asymmetrical, and mostly mediated by males. Assignment procedures detected some cases of interchange and individuals of admixed ancestry between breeding grounds, indicating limited mixing of individuals between these stocks. Overall, results highlight the differentiation of humpback whale breeding populations with adjacent feeding grounds. This appears to be a remarkable example of fidelity to seasonal habitat in the absence of any contemporary barriers.